Hidradenitis Suppurativa and 1-Carbon Metabolism: Role of Gut Microbiome, Matrix Metalloproteinases, and Hyperhomocysteinemia - Molnar, Jack; Mallonee, Carissa Jo; Stanisic, Dragana; Homme, Rubens P.; George, Akash K.; Singh, Mahavir; Tyagi, Suresh C. (Frontiers in Immunology, 2020)
Hidradenitis suppurativa (HS) is a chronic, inflammatory skin condition characterized by painful nodules which suppurate and later develop into scar tissues followed by the development of hypodermal tracts. Although the mechanisms behind HS are not fully understood, it is known that dietary factors play important roles in flare frequency and severity. We hypothesize that the high fat diet (HFD) causes dysbiosis, systemic inflammation, and hyperhomocysteinemia (HHcy) in susceptible individuals, which subsequently elevate inflammatory cytokines such as IL-1β, IL-6, IL-17, and tumor necrosis factor alpha (TNF-α). This increase in dysbiosis-led inflammation coupled with a dysregulation of the 1-carbon metabolism results in an increase in matrix metalloproteinases MMP-2, MMP-8, and MMP-9 along with tissue matrix remodeling in the development and maintenance of the lesions and tracts. This manuscript weaves together the potential roles played by the gut microbiome, HHcy, MMPs, and the 1-carbon metabolism towards HS disease causation in susceptible individuals.